Insulin resistance and central obesity determine hepatic steatosis and explain cardiovascular risk in steatotic liver disease - Semmler, Georg; Balcar, Lorenz; Wernly, Sarah; Völkerer, Andreas; Semmler, Lorenz; Hauptmann, Laurenz; Wernly, Bernhard; Aigner, Elmar; Niederseer, David; Datz, Christian (Frontiers in Endocrinology, 2023)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) has recently been proposed to replace (non)-alcoholic fatty liver disease and focus on patients with progressive disease due to the presence of metabolic dysfunction. However, it is unclear whether the new definition actually identifies patients with hepatic steatosis at increased cardiovascular risk. Methods: 4286 asymptomatic subjects from the SAKKOPI study aged 45-80years undergoing screening colonoscopy were analyzed. Steatosis was diagnosed by abdominal ultrasound. MASLD was diagnosed according to the recent expert-consensus. Insulin resistance was assessed by HOMA-IR (cut-off: ≥2.5), subclinical inflammation was estimated by ferritin/CRP/uric acid, cardiovascular risk was assessed using SCORE2/ASCVD. Results: Mean age was 59.4±8.5 years, 51.6% were male, mean BMI was 27.0±4.5 kg/m², 9.2% had type 2 diabetes mellitus. 1903 (44.4%) were diagnosed with hepatic steatosis, and were characterized by more severe metabolic dysfunction including insulin resistance (47.1% vs. 12.2%, p<0.001) and central obesity (waist circumference ≥102/88 cm, 71.8% vs. 37.1%, p<0.001). This translated into higher (subclinical) inflammation (ferritin 153 vs. 95 mg/dL, p<0.001,uric acid 6.3 vs. 5.2 mg/dL, p<0.001) and 10-year cardiovascular risk (SCORE2 7.8 vs. 5.1 points, p<0.001, ASCVD 17.9 vs. 10.8 points, p<0.001). 99.0% of subjects with steatosis met the MASLD definition, 95.4% met the MAFLD definition, and 53.6% met the definition of metabolic syndrome while 95.4% of subjects without steatosis also met the MASLD criteria for metabolic dysfunction compared to 69.0% and 17.4% who met the MAFLD and metabolic syndrome criteria, respectively. Forward stepwise regression indicated that waist circumference, HOMA-IR, and triglycerides were most relevant in explaining the presence of hepatic steatosis across all subgroups of increasing metabolic dysfunction. At the same time, hepatic steatosis was not associated with cardiovascular risk in the overall cohort (SCORE2: B=0.060, 95%CI: -0.193-0.314, p=0.642) and in patients with metabolic dysfunction after adjusting for age, sex, and these 3 metabolic dysfunction components. Conclusion: While hepatic steatosis is associated with increased central obesity and insulin resistance, metabolic dysfunction per se rather than hepatic steatosis explains cardiovascular risk in these patients.